Fostering Collective Efficacy?: What School Leaders Should Know - Hoogsteen, T.J. (Advances in Social Sciences Research Journal, 2021)
Statements claiming that efforts of policy makers, system and school leaders, and staff developments toward education reforms might be better served by strategically and intentionally considering how to foster collective efficacy throughout the conceptualization, design, delivery, and assessment of change initiatives (Donohoo, 2018, p. 340) have led schools and districts to attempt to do just that. However, such conclusions may not be justified. The present review examines available research using a framework inspired by Willingham (2012) which is meant to guide leaders in evaluating the trustworthiness and value of research. Willingham (2012) notes that leaders should be able to recognize the change when it happens, know how large the change should be, and estimate the length of time the change will take. This framework is applied to CTE literature to gauge whether the research base surrounding collective teacher efficacy is useful to school and district leaders when making decisions regarding school improvement and organizational change initiatives. The article concludes with suggestions for future research.